Challenges to the implementation of malaria policies in Malawi - Chikondi A. Mwendera; Christiaan de Jager; Herbert Longwe; Save Kumwenda; Charles Hongoro; Kamija Phiri; Clifford M. Mutero (BMC, 2019)
Abstract Background Despite malaria prevention initiatives, malaria remains a major health problem in Malawi, especially for pregnant mothers and children under the age of five. To reduce the malaria burden, Malawi established its first National Malaria Control Programme in 1984. Implementation of evidence-based policies contributed to malaria prevalence dropping from 43% in 2010 to 22% in 2017. In this study, we explored challenges to implementing malaria policies in Malawi from the perspective of key stakeholders in the country. Methods In this qualitative study, we conducted in-depth interviews with 27 key informants from April to July 2015. We stopped sampling new participants when themes became saturated. Purposive and snowballing sampling techniques were used to identify key informants including malaria researchers that were policy advisors, policy makers, programme managers, and other key stakeholders. Interviews were conducted in English, recorded and transcribed, and imported into QSR Nvivo 11 for coding and analysis. Data were analysed using the qualitative content analysis approach. Results Participants identified three main categories of challenges to the implementation of malaria policies. First structural challenges include inadequate resources, unavailability of trained staff, poor supervision and mentorship of staff, and personnel turnover in government. The second challenge is unilateral implementation of policies. The third category is the inadequately informed policy development and includes lack of platforms to engage with communities, top-down approach in policy formulation and lack of understanding of socio-cultural factors affecting policy uptake by communities. Conclusions Policy makers should recognize that inadequate support of policy objectives leads to an implementation gap. Therefore, policy development and implementation should not be viewed as distinct, but rather as interactive processes shaping each other. Support for health policy and systems research should be mobilized to strengthen the health system. Detailed assessment of implementation challenges to specific malaria policies should also be conducted to address these challenges and support the shift from the paradigm of malaria prevention and control to elimination in Malawi.